Study on Suspension System for HXN5 Diesel Locomotive Bogie - TANShao-jun; LUO Yun; YANGYong-jun (机车电传动)
Dynamic performance of HXN5 type diesel locomotive was evaluated, and adaptability of the suspension system parameter and its effect on dynamic performance of HXN5 locomotive was analyzed. Based above, suggestions of suspension parameters optimization were put forward.